PET containers in Brazil: Opportunities and challenges of a logistics model for post-consumer waste recycling - Coelho, T. M. [UNESP]; Castro, R. [UNESP]; Gobbo, J. A. [UNESP] (Elsevier B.V., 2011)
The use of post-consumer materials is directly related to reducing the cost of production and extraction of natural resources. Non-recyclable materials are randomly disposed in the environment. Brazil is one of the largest consumers of PET (polyethylene terephthalate) bottles. The purpose of this paper is to describe the opportunities and challenges of the logistics model for post-consumer PET bottle recycling in Brazil, while providing knowledge of its practices along the recycling chain. The results describe the need to educate those directly and indirectly involved in the process: to reduce consumption in order to reduce the amount of waste generated: to structure the post-consumer reverse chain and engage industrial sectors and government, through public policies, to support cleaner technologies along the PET bottle production chain. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: PET bottles; Reverse logistics; Recycling